Modified polyol-mediated synthesis of Sr- and W-substituted La2Mo2O9 solid electrolyte for solid oxide fuel cells - Pandey R.; Singh S.; Singh P. (My University, 2025)
The oxide-ion conducting system (La1−xSrx)2Mo1.5W0.5O9−δ with x = 0.00, 0.02, 0.05 and 0.07 were prepared for the first time by modified polyol-mediated synthesis method. The structural properties and electrical conductivity of this system (La1−xSrx)2Mo1.5W0.5O9−δ were studied using XRD, DT/TGA, SEM, XPS, BET, TEC and EIS characterization techniques. It was found that doping of Sr and W together at La and Mo site, respectively, stabilizes the cubic β-phase of La2Mo2O9 at room temperature. The electrical conductivity of system was found to be maximum for x = 0.05 doping of Sr at La site in (La1−xSrx)2Mo1.5W0.5O9−δ. In dilatometry measurement, TEC was found to be 13.9 × 10–6/°C for the compositions x = 0.05 which is compatible with a few other reported components of the intermediate temperature solid oxide fuel cell (IT-SOFC). This synthesis route also helps for the preparation of fine grains, high specific surface area and reduced particle size at relatively lower calcination temperatures. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.